THE USE OF FREEWRITING TECHNIQUE ON THE POETRY WRITING ABILITY - Nursyaidah, Nursyaidah - (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Poetry writing skills require creativity, imagination, and mastery of language. The freewriting technique, which allows writers to write without constraints during a set period of time, is considered effective in overcoming writing barriers and generating creative ideas. This study aims to determine the impact of using the freewriting technique on students' poetry writing skills, using a descriptive qualitative approach. Data were collected through observation, interviews, and analysis of students' poetry works. The results of the study show that the freewriting technique is effective in enhancing creativity, self-expression, and reducing barriers in poetry writing.